Statistical Technique in Gas Dispersion Modeling Based on Linear Interpolation - M. S. Azwan Ramli; M. Shukri Z.A (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In this paper, we introduced statistical techniques in creating a gas dispersion model in an indoor with a controlled environment. The temperature, air-wind and humidity were constant throughout the experiment. The collected data were then treated as an image; which the pixel size is similar to the total data available for x and y axis. To predict the neighborhood value, linear interpolation technique was implemented. The result of the experiment is significantly applicable in extending the total amount of data if small data is available.